KELAYAKAN FILM DOKUMENTER BERBASIS TUMBUHAN LOKAL SEBAGAI MEDIA PEMBELAJARAN MATERI KEANEKARAGAMAN HAYATI KELAS X - Rexy Maulana Dwi Karmadi; Syamswisna Syamswisna; Reni Marlina (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
Abstract This research aimed to determine the feasibility of local plant-based documentary film as instructional media for learning biodiversity in class X. The method used in this research was descriptive method with quantitative research form. In documentary film validation, there was 5 material aspects measured, namely the suitability of material with curriculum, the suitability of material with learning purpose, material order, material quality, and language, then 6 media aspects measured, namely technical quality, narration, music and sound effects, consistency, visualization, and presentation. Documentary film was validated by 3 material experts and 3 media experts. Material experts were lecturer of Biology Education Studies Program in FKIP Untan, biology teacher in class X SMAN 1 Tebas, and biology teacher in class X SMAN 2 Tebas, then media experts were instructional media programmer and desaigner in Borneo Animation School MIP, craft teacher in SMAN 1 Tebas, and physics teacher in SMAN 2 Tebas. The validation result by material experts and media experts were RTVtk 3.84 and 3.42 with valid categories, so the local plant-based documentary film was feasible to be used as instructional media for learning biodiversity in class X. Keywords: Biodiversity, Documentary film, Feasibility